Pengaruh Insentif, Iklim Organisasi Dan Kepuasan Kerja Terhadap Komitmen Kerja Pegawai - Mutiara Ayu Hermawan (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
The background of this research is that the incentives given are not in accordance with the wishes of the employees. Inadequate amount of incentives given, sometimes the timing of the incentives is not in accordance with a predetermined date. organizational climate is still not optimal. Leaders are still not consistent in giving assignments. sometimes the tasks given by the leadership are far outside the employee's working hours. Employees face many job risks that are not taken into account the causes and consequences. employee job satisfaction has not been achieved, where there are still many employees who feel dissatisfied. Employee work discipline is still not optimal. not a few employees who come to work outside the hours that have been set. many employees are not yet committed to their work, service orientation is still not optimal. Employee integrity is still not optimal. Thus, the purpose of this study was to determine the effect of incentives, organizational climate and job satisfaction on the work commitment of UPTD employees at the Manonjaya Health Center, Tasikmalaya Regency. The research method is descriptive quantitative, with the results of incentive research tending to be good as well as job satisfaction tending to be good. However, incentives have no significant effect on the work commitment of UPTD Manonjaya Health Center employees. This means that if the provision of incentives is increased, it will not have a significant effect on employee work commitment. The smallest value of the respondent's response to the incentive variable is an indicator of social incentives, while the highest value is found in the non-material incentives indicator. Organizational climate tends to be good as well as job satisfaction tends to be good. Thus, organizational climate has a significant effect on the work commitment of UPTD Manonjaya Health Center employees. This means that if the organizational climate is improved, it will have an impact on increasing work commitment. The smallest value of the respondent's response to the organizational climate variable is an indicator of conflict, while the highest value is found in the indicator of warmth between employees. . Job satisfaction tends to be good as well as job satisfaction tends to be good. However, job satisfaction has no significant effect on the work commitment of UPTD Manonjaya Health Center employees. This means that if job satisfaction is increased, it will not have a significant impact on increasing work commitment. The smallest value of the respondent's response to the variable job satisfaction is an indicator of turnover, while the highest value is found in the indicator of responsibility. Providing incentives, organizational climate and job satisfaction affect the work commitment of UPTD Manonjaya Health Center employees. This means that if the provision of incentives, organizational climate and job satisfaction is increased then work commitment will also increase